HAK ASASI MANUSIA DALAM AT-TAARUDH AL-ADILLAH: MENCARI TITIK TEMU ANTARA SYARIAH DENGAN KEADILAN UNIVERSAL - Fandiyah, Fina; Andrianti, Elma Suci; Muttaqin, M. Imamul (Anfa Mediatama, 2024)
This study explores human rights within the context of ta'arudh al-adillah, focusing on the endeavor to find common ground between Sharia principles and the concept of universal justice. Employing a qualitative approach, the study examines various written sources, including books, journals, articles, and electronic resources. The findings reveal the potential for alignment between Sharia and human rights norms through reinterpreting and contextualizing the fundamental principles of both frameworks. The study argues that an inclusive approach can yield a more just and humane legal framework, one that accommodates religious values while respecting individual rights. The research outcomes are expected to contribute to the development of legal thought capable of bridging the gap between Sharia law and international justice standards, and to support the protection of human rights in pluralistic societies.